A role for astrocytes and microglia in synapse loss in Alzheimer's disease. (1st February 2022) - Tzioras, Makis; Daniels, Michael; Davies, Caitlin; Hooley, Monique; He, Xin; Dando, Owen R.; Hardingham, Giles; McColl, Barry; Spires‐Jones, Tara L.
Abstract: Background: Neuropathologically, synapse loss correlates most strongly with the progressive cognitive decline observed in Alzheimer's disease (AD). Despite strong evidence from genetic studies implicating changes in glia as important for disease risk, we are only beginning to understand the role that microglia and astrocytes play in synapse degeneration in AD. Method: In this study, we have used high resolution imaging of post‐mortem brain tissue to examine whether glia contain synaptic proteins in AD. Cultures of primary mouse and human microglia were exposed to pHrodo‐tagged synapses from human AD or control post‐mortem brain for phagocytosis assays. Mouse models expressing AD associated genes were used for RNA sequencing and translating ribosomal affinity purification (TRAP) followed by RNA sequencing. Result: We observe both astrocytes and microglia contain synaptic proteins in human AD more than in control brain. Cultured microglia phagocytose synapses from AD brain more and faster than those from control brain. RNA sequencing in AD model mice revealed strong increases neuroinflammatory signals including transcripts expressed in microglia and astrocytes and decreases in transcripts related to synaptic function. When examining the astrocyte specific changes with TRAP, we observed increases in phagosome and lysosome related pathways. Conclusion: Together, our results indicate that microglia and astrocytes play a role in synapse degeneration or clearance of dead synapses in Alzheimer's disease.